Some Conditions for the Boundedness of Commutators of Fractional Integrals on Generalized Weighted Morrey Spaces - Ramadana, Yusuf (Program Studi Matematika, Universitas Nusa Cendana, 2025)
In this paper, we investigate the boundedness of commutators generated by bBMO and fractional integrals I_α from M_ψ_1^p,w^p to M_ψ_2^q,w^q for 1<p<q<∞. We obtain some new conditions for the pair (ψ_1,ψ_2) of the functions ψ_1 and ψ_2 on R^n× (0,∞) that ensure the boundedness properties.